Probing the mechanism of baylis-hillman reaction in ionic liquids - Singh, Anshu; Kumar, Anil (Journal of Organic Chemistry, 2012)
The kinetic data for a Baylis-Hillman reaction in certain ionic liquids possessing ethylsulfate anion [EtSO4](-) demonstrate that the rate determining step (RIDS) is second order in aldehyde, but first order in acrylate and DABCO. This observation is similar to the one made by McQuade et al., who carried out this reaction in an aprotic polar solvent like DMSO. However, this is in contrast to the general observation that ADS is first order in aldehyde, acrylate, and DABCO in organic solvents.